Implementasi Peraturan Pemerintah Nomor 13 Tahun 2016 Tentang Bantuan Stimulan Perumahan Swadaya (Studi Kasus di Dinas Pekerjaan Umum Dan Perumahan Rakyat Kabupaten Aceh Singkil) - Muhir Muhir; Nellis Mardhiah (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The self-help housing stimulant assistance program (BSPS) is an effort by the government to assist the implementation of the construction of decent houses or housing in a healthy and safe environment independently. This program aims to help the community to have a healthy, safe and comfortable home. The purpose of this study was to determine the implementation of the self-help housing stimulant program at the Department of Public Works and Public Housing, Aceh Singkil Regency. The research method used is descriptive-qualitative method, where data collection uses observation and interview techniques in the form of written or spoken words from the people or actors observed. The Aceh Singkil Regency Self-Help Stimulant Housing Assistance Program (BSPS) is running well, but there are some that cannot be overcome in the implementation of the stimulant assistance program, in the sense that this program is almost completely running smoothly.